(untitled) (The Review of Diabetic Studies, 2024)
Background Healthcare-associated infections (HAIs) pose a significant global challenge in clinical environments, affecting 7-10% of patients in high-income countries and up to 15% in low- and middle-income settings, with approximately 136 million resistant cases annually straining resources and increasing mortality. Frontline providers face elevated risks from occupational exposures to pathogens like MRSA and CRE, necessitating robust infection control measures including hand hygiene, PPE, and environmental decontamination.​ Methods: This narrative review synthesizes evidence from historical milestones, CDC/WHO guidelines, point prevalence surveys, and outbreak investigations detailed in the document "Protecting Patients and Providers: Infection Control in Clinical Environments." It examines pathogens, transmission dynamics, standard precautions, surveillance systems, and tailored protocols across hospitals, ICUs, ORs, EDs, and long-term care, incorporating multimodal interventions and economic analyses.​ Results: Standard precautions and bundles reduced HAIs by 40-60%, with hand hygiene compliance improving from 20-40% to 60-80% via multimodal strategies; VAP bundles cut incidence by 50%, while investments in IPC yielded 21-98 returns per dollar. Surveillance like NHSN enabled 50% HAI declines, though challenges persist in LMCs due to overcrowding and AMR.​ Conclusions: Strengthening infection control through evidence-based bundles, stewardship, and equity-focused adaptations can substantially mitigate HAIs, protecting patients and providers while optimizing healthcare systems. Sustained multimodal efforts remain essential amid emerging threats.​